(untitled) (Ozone Therapy Global Journal, 2015)
Introduction: the chronic low-back pain caused by stenosis of the lumbar spinal canal is a problem not yet solved. Purposes: demonstrate the effectiveness of the Lumbar Epidural Ozonolysis by catheterization in the treatment and control of low-back pain due to stenosis of the spinal canal, and its effectiveness in the decompression of neurovascular structures occupying the canal. Methods: we studied 17 patients between 45 and 75 years of age, treated in the pain unit of the Valencian Institute of ozone therapy with lumbar epidural ozonolysis by catheterization, between October 1st 2011 and May 31st 2014, both included, with a diagnosis of chronic low back pain due to spinal canal stenosis. The variables studied were: age, sex, causes and results according to the index of Oswestry as an evaluation instrument. Results: there was a predominance of the female sex, the most common age groups were 40 to 50 years and 70 years or older. The Oswestry index and the visual analog scale of pain showed improvement from the first week post-treatment and 94.1% of good results was obtained. Conclusions: it shows that the ozone through the epidural, exerts an important function on the canal decompression….